Innovate to Liberate: Akselerasi Kreativitas Siswa dalam Pendidikan - Crisvin; Masduki Asbari; Jacelyn Valencia Chiam (AGUSPATI RESEARCH INSTITUTA, 2023)
The aim of this study is to identify the role of the teacher's paradigm in enhancing student creativity within the